Association of dietary habits with obesity among school adolescents in Central India - Namdev, Garima; Mishra, Mahesh Kumar; Narkhede, Vinod (International Journal Of Community Medicine And Public Health, 2019)
Background: The growing prevalence of obesity among school adolescents is a major public health concern. It can be seen mostly as a result of modifiable risk factors like lack of required physical activity and rapid change in dietary habits among them. Methods: The present cross sectional descriptive study was done among adolescents studying in schools (government and private) of Bhopal city. School adolescents were classified as obese and non-obese as per the WHO criteria used for obesity in South East Asia Region (SEAR). Pre-tested, self-administered questionnaire was used to collect data which comprised of socio demographic information and various dietary habits like frequent consumption of fast & fried food, bakery products and little dietary behavior. Results: Out of total 6.6% obese school adolescents, majority of them consume fast foods (82%), fried foods (89%) and bakery products (79.5%) and all of these were positively associated with increased risk of obesity. Few eating behaviours like skipping breakfast, frequent snacking and eating outside were also found positively associated. Conclusions: There is definitely a major role of dietary habits for increased risk of obesity among school adolescents. So, it is the need of hour to create awareness among school adolescents regarding their dietary habits.